2013
DOI: 10.3329/ijarit.v2i2.14009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Density on Growth and Production Performance of Indigenous Stinging Catfish, Heteropneustes fossilis (Bloch)

Abstract: An on-farm experiment was undertaken in nine earthen ponds to evaluate the growth and production potentials of stinging catfish shing, Heteropneustes fossilis for the period of six months from March to August 2010. Three stocking densities such as 1,25,000 (T1), 1,87,500 (T2) and 2,50,000 ha-1 (T3) were tested with three replications each. Fish were fed with commercial pelleted feed containing 35% crude protein. After six months rearing, the mean harvesting weights of shing were 69.42±6.20, 58.74±3.85 and 49.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 7 publications
9
17
0
Order By: Relevance
“…The mean value of dissolved oxygen in water varied from (4.47 ± 0.10) (T 3 ) to (4.53 ± 0.08) mg/L (T 2 ) in the present study. This finding strongly agreed with Kohinoor et al [20] who measured the dissolved oxygen of 4.23 to 5.32 mg/L in H. fossilis culture ponds.…”
Section: Discussionsupporting
confidence: 82%
“…The mean value of dissolved oxygen in water varied from (4.47 ± 0.10) (T 3 ) to (4.53 ± 0.08) mg/L (T 2 ) in the present study. This finding strongly agreed with Kohinoor et al [20] who measured the dissolved oxygen of 4.23 to 5.32 mg/L in H. fossilis culture ponds.…”
Section: Discussionsupporting
confidence: 82%
“…The percentage of survival as recorded in the present study was similar as reported by Kohinoor et al, (2012).…”
Section: Resultssupporting
confidence: 80%
“…Considering its status it is essential to develop a suitable culture technique in Bangladesh. However, very little published literature are available on growth and production of stinging catfish in pond, cistern and net cages in Bangladesh (Haque et al, 1988;Khan et al, 2003;Narejo et al, 2005 andKohinoor et al, 2012). This is an excellent fish for culture in derelict water bodies as it is able to live in poorly oxygenated water due to its capacity to exchange via accessory respiratory organ (Singh and Hughes, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results obtained by Dhawan and Kaur (2002); Okbah and Gohary (2002). Kohinoor et al (2012) reported that the similar range of pH value even suitable for catfish culture ( , 1997). The studied values were lower DO in the MCRT-2 and 3 in the later summer to early part of monsoon may be the result of decomposition of plankton and autochthonous organic maters.…”
Section: Resultssupporting
confidence: 78%